2013
DOI: 10.1063/1.4794289
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of insonated contrast agents: Saturation and transient break-up

Abstract: Under insonation contrast agents are known to perform nonlinear pulsations and deform statically, in the form of buckling, or dynamically via parametric mode excitation, and often exhibit jetting and break-up like bubbles without coating. Boundary element simulations are performed in the context of axisymmetry in order to establish the nonlinear evolution of these patterns. The viscoelastic stresses that develop on the coating form the dominant force balance tangentially to the shell-liquid interface, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
1
20
0
4
Order By: Relevance
“…They observed mainly subharmonic shape mode excitation when the forcing frequency was twice the natural frequency of the shape mode, in agreement with results based on linear stability analysis (Tsiglifis & Pelekasis 2011). Tsiglifis & Pelekasis (2013) performed boundary integral simulations of pulsating contrast agents, while ignoring viscous effects on the liquid side, in view of the relatively large shell viscosity and the typical small size of encapsulated bubbles. They captured harmonic and subharmonic shape mode excitation during the compression phase of the pulsation, for the parameter range predicted by linear stability (Tsiglifis & Pelekasis 2011).…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…They observed mainly subharmonic shape mode excitation when the forcing frequency was twice the natural frequency of the shape mode, in agreement with results based on linear stability analysis (Tsiglifis & Pelekasis 2011). Tsiglifis & Pelekasis (2013) performed boundary integral simulations of pulsating contrast agents, while ignoring viscous effects on the liquid side, in view of the relatively large shell viscosity and the typical small size of encapsulated bubbles. They captured harmonic and subharmonic shape mode excitation during the compression phase of the pulsation, for the parameter range predicted by linear stability (Tsiglifis & Pelekasis 2011).…”
Section: Introductionsupporting
confidence: 80%
“…Numerical simulations of pulsating coated microbubbles with the boundary element methodology (Tsiglifis & Pelekasis 2013), when potential flow is considered in the surrounding liquid, recover a tendency for preferential excursion from equilibrium during compression due to nonlinear interactions between emerging shape modes during compression, as a manifestation of harmonic or subharmonic excitation (see also Tsiglifis & Pelekasis (2011) for an extensive analysis of this mechanism of shape mode excitation of coated microbubbles) and the breathing mode of pulsation; the latter term refers to volume pulsations of the bubble. Nevertheless, the extent of the compression amplitude obtained by the simulations performed in the latter study was smaller than the one reported from optical measurements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is assumed to be infinitely thin and isotropic in their planes. The elasticity of the membrane can be described by the Mooney-Rivlin law [46] …”
Section: Dynamics Of the Coating Membranementioning
confidence: 99%